(untitled) (Biological Sciences - PJSIR, 2005)
The liquid-liquid equilibrium data are presented for phase behaviour of ternary system of water, acetic acid and alkanols (1-butanol, 1-pentanol and 1-hexanol) at the temperature of 30±0.1 °C. From the data, binodal curves, tie lines, plait points and equilibrium distribution diagram were determined experimentally, and the distribution coefficients and separation factors were computed, with a view to examine the suitability of alcoholic solvents to extract acetic acid from its aqueous solution. It has been found that the solubility of acetic acid increased with the increasing number of carbon atoms in the chain of the alcohol used as the solvent, giving higher values of distribution coefficients and the separation factor.